Diabetes-related weight change in a Canadian First Nation cohort - ND Riediger; V Lukianchuk; J Roulette; LM Lix; L Elliott; SG Bruce (International Journal of Circumpolar Health, 2017)
The Canadian First Nations population is disproportionately burdened by diabetes and diabetes complications. Body weight management is purported to be important in the prevention and management of diabetes. In this study, we sought to describe weight change in a First Nation cohort according to diabetes status and management. Study data were from two diabetes screening studies in Sandy Bay First Nation in Manitoba, Canada, collected in 2002/2003 (baseline) and 2011/2012 (follow-up). The cohort was composed of respondents to both screening studies (n=171). Fasting blood samples, anthropometric, health and demographic data were collected. At baseline, 24.8% (n=41) of the cohort members had diabetes. At follow-up, an additional 20.6% (n=34) developed diabetes. Among all participants with diabetes (long-term and incident cases), 66.6% lost weight between the two study periods. Among only participants with long-term diabetes (>8 years), 31.7% lost >10 kg. HbA1c at baseline, positive change in HbA1c over time, and use of metformin were significantly associated with weight loss ≥5%, independent of age, sex, and BMI at baseline. Further research is needed to better understand if and how diabetes-related weight loss contributes to morbidity and mortality in this First Nation population.